2021
DOI: 10.1021/acs.jmedchem.0c01715
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Dissection of Potency and Selectivity of Cytosolic Hsp90 Inhibitors

Abstract: The cytosolic Hsp90-selective inhibitor TAS-116 has an acceptable safety profile and promising antitumor activity in clinical trials. We examined the binding characteristics of TAS-116 and its analogs to determine the impact of the ligand binding mode on selectivity for cytosolic Hsp90. Analyses of the co-crystal structure of Hsp90 and inhibitor TAS-116 suggest that TAS-116 interacts with the ATP-binding pocket, the ATP lid region, and the hydrophobic pocket. A competitive isothermal titration calorimetry anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…8,9 Pimitespib (TAS-116) is an oral HSP90 inhibitor that selectively binds to cytoplasmic HSP90a and HSP90b. 10,11 Pimitespib inhibits growth and induces apoptosis in both imatinib-sensitive and -resistant GIST cell lines and reduces autophosphorylated mutated KIT in the Golgi apparatus. 12 A first-in-human phase I study determined the recommended dose of pimitespib and demonstrated its acceptable toxicity profile and promising clinical activity in patients with advanced solid tumors, including GIST.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Pimitespib (TAS-116) is an oral HSP90 inhibitor that selectively binds to cytoplasmic HSP90a and HSP90b. 10,11 Pimitespib inhibits growth and induces apoptosis in both imatinib-sensitive and -resistant GIST cell lines and reduces autophosphorylated mutated KIT in the Golgi apparatus. 12 A first-in-human phase I study determined the recommended dose of pimitespib and demonstrated its acceptable toxicity profile and promising clinical activity in patients with advanced solid tumors, including GIST.…”
Section: Introductionmentioning
confidence: 99%
“…The position of the lid controls the accessibility of ligands to certain regions of the binding site . To extract general, state-specific binding hotspots, we probed whether the three major lid conformations form distinct binding-site surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…The position of the lid controls the accessibility of ligands to certain regions of the binding site. 58 To extract general, state-specific binding hotspots, we probed whether the three major lid conformations form distinct binding-site surfaces. To find such hotspots, we calculated how often residues occurred within 5 Å of ligands bound to each lid conformation ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, both inhibitor binding and HSP90 chaperone cycles lead to large conformational changes in the flexible structure of HSP90 [ 26 , 27 , 28 ], which makes the design of a drug that can relieve side effects challenging. Moreover, multiple reports have indicated that the conformational changes in the N-terminal ATP site of HSP90 play a key role in the inhibition of ATP hydrolysis and client processing [ 29 , 30 , 31 , 32 ]. It is well known that the thermodynamics and kinetics of conformational changes are essential for gaining insights into the molecular mechanism of inhibitor–HSP90 binding and for the development of clinically available drugs against cancers [ 33 ].…”
Section: Introductionmentioning
confidence: 99%